Assessment of Municipal Plastic Waste and Recycling Systems in Pokhara, Nepal: Current Status, Challenges, and Sustainable Management Approaches - K.C, Dikpal; Khanal, Rishav; Tiwari, Saugat; Baral, Sanjay (Himalayan Journal of Applied Science and Engineering, 2026)
Plastic waste, largely composed of non-biodegradable petroleum-based polymers, has become a growing environmental and public health challenge in Pokhara Metropolitan City (PMC), Nepal. This study assesses plastic waste generation and recycling practices using four estimation approaches: household waste sampling, landfill volume density assessment, data from private waste contractors, and population based per-capita calculations. Findings from a survey of 400 households indicate that PMC generates nearly 11227.847 metric tons of plastic waste annually, with plastic comprising 16.86% of total municipal solid waste and Low-Density Polyethylene (LDPE) contributing the highest share due to its widespread use in packaging. At present, only 10.86% of this waste is recycled by existing private facilities. Economic and technical analysis shows that a well-equipped recycling center operated by at least three workers with one machine could recycle about 218.4 metric tons of plastic per year, reduce 582.4 metric tons of Greenhouse Gas (GHG) emissions, save 1,517 m³ of landfill space, and create meaningful revenue opportunities. Overall, the results emphasize the need for integrated waste management, improved source-level segregation, and increased investment in recycling infrastructure. Strengthening these systems can enhance environmental protection, reduce landfill pressure, support local employment, and contribute to long-term sustainability in PMC.